Tainted: An olfaction-enhanced game narrative for smelling virtual ghosts. Issue 125 (May 2019) - Ranasinghe, Nimesha; Koh, Koon Chuan Raymond; Tram, Nguyen Thi Ngoc; Liangkun, Yan; Shamaiah, Kala; Choo, Siew Geuk; Tolley, David; Karwita, Shienny; Chew, Barry; Chua, Daniel; Yi-Luen Do, Ellen
Highlights: Tainted is a first-person 3D adventure game that enables players to experience a traditional horror folklore using visual-auditory-olfactory interactions. The information provided by the additional olfactory stimuli delivers an immersive gaming experience by providing game narrative and signaling predefined game conditions (e.g. imminent threat, game hints). Smell stimuli also stimuli attempt to invoke emotional responses such as fear and curiosity. It is suggested that the olfactory information is closely coupled with players' experience and enjoyment of the narrative as well as the smell-driven gameplay. Abstract: This paper presents "Tainted", a first-person 3D adventure game that enables players to experience a traditional horror folklore using visual-auditory-olfactory interactions. The system consists of a computer to play the game and a smell-emitting module that contains four different scents (jasmine, pineapple, mango and banana). The information provided by the additional olfactory stimuli delivers an immersive gaming experience by providing game narrative and signaling predefined game conditions (e.g. imminent threat, game hints). At the same time, smell stimuli attempt to invoke emotional responses such as fear and curiosity. Experiments were carried out to 1) validate the design of the device and 2) measure user enjoyment and experience with and without the added smell feedback using an adapted questionnaire from the GameFlow model. The results show that the provided olfactory stimuli are more informative to users and provoked greater emotions, as compared to the use of visual and auditory cues alone. The majority of participants preferred to have the added feedback device in the game (95% neutral and positive). However, approximately 26% of participants also noted that the smells are not distinct from each other. Nevertheless, it is suggested that the olfactory information is closely coupled with players' experience and enjoyment of the narrative, as well as the smell-driven gameplay. Future studies of these factors will enable us to establish a framework to support multisensory game developers in the design of olfaction-enhanced games and other multimedia applications.